Role of cardiovascular imaging in systemic autoimmune diseases - Sitia, Simona (Baishideng Publishing Group Co., Limited, 2010)
Systemic autoimmune diseases are characterized by an excess of cardiovascular (CV) morbidity and mortality compared to the general population, mainly due to chronic inflammation that promotes the development of endothelial dysfunction and enhanced atherosclerosis. Early diagnosis of silent CV involvement is mandatory to improve the long term prognosis of these patients and CV imaging provides valuable information as a reliable diagnostic tool. Transthoracic echocardiography, with several applications (e.g. coronary flow reserve evaluation, tissue Doppler imaging, speckle tracking and the transesophageal approach), represents a first line evaluation, in association with biomarkers of endothelial dysfunction, such as asymmetric dimethylarginine. Nuclear medicine provides useful information on myocardial perfusion. The aim of this editorial is to provide a brief but complete review of the diagnostic tools available for screening and follow up of CV involvement in systemic autoimmune diseases.